Morphological Characteristics Of Morphometric Parameters Of The Gastric Mucosa In Polypragmasia With Anti-Inflammatory Drugs - Toshmamatov B. N; Teshaev Sh.J; Xudoyberdiyev D.K (Genius Publishing Group, 2022)
Morphological changes in the coolant and the pathogenesis of chronic gastritis of the disease have their own characteristics for different forms of gastritis [2.4]. It is generally recognized that Helicobacter pylori – associated gastritis is most common, however, the so-called NSAID–gastropathy (one of the varieties of chemical gastritis, type C) is no less relevant - damage to the gastric mucosa caused by taking nonsteroidal anti-inflammatory drugs (NSAIDs).
Keywords: Morphological changes; NSAID; different; pathogenesis